Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00406-005-0606-6
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in prisoners: risk factors and relevance to suicidal behaviour. A prospective case–control study

Abstract: A family history of suicidal behaviour, history of psychiatric hospitalisation and symptoms of anxiety or depression were independent risk factors for SI in prisoners. Inmates with SI had a higher risk for self-destructive acts at follow-up. Inmates with SI are a high-risk group for future self-destructive acts, so special precautions designed to reduce this risk are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 39 publications
1
45
1
11
Order By: Relevance
“…The MADRS is increasingly employed in clinical research because studies have shown that the scale may be superior to other scales with respect to sensitivity to change (Montgomery &´ Asberg, 1979) and other psychometric properties, especially regarding populations with physical disease (Kearns et al, 1982), as it includes fewer somatic items. MADRS has been translated into Greek and has been used with Greek psychiatric patients as well as for specific populations (Lekka, Argyriou, & Beratis, 2006). The internal consistency coefficients (Cronbach's alphas) for MADRS obtained from our sample were .86 for the patients and .62 for the controls, which reflects the fact that the scale variance was higher for the patients, thereby increasing the magnitude of the correlations.…”
Section: Assessmentsmentioning
confidence: 75%
“…The MADRS is increasingly employed in clinical research because studies have shown that the scale may be superior to other scales with respect to sensitivity to change (Montgomery &´ Asberg, 1979) and other psychometric properties, especially regarding populations with physical disease (Kearns et al, 1982), as it includes fewer somatic items. MADRS has been translated into Greek and has been used with Greek psychiatric patients as well as for specific populations (Lekka, Argyriou, & Beratis, 2006). The internal consistency coefficients (Cronbach's alphas) for MADRS obtained from our sample were .86 for the patients and .62 for the controls, which reflects the fact that the scale variance was higher for the patients, thereby increasing the magnitude of the correlations.…”
Section: Assessmentsmentioning
confidence: 75%
“…La moyenne du score de dépression à la BDI est de Les idées suicidaires sont liées avec l'histoire des hospitalisations psychiatriques [18,12] ou troubles psychiatriques actuels, notamment les hallucinations [14,20,29], aux troubles addictifs [20,29] et à un fort taux d'anxiété [18]. Cela est plus significatif pour les hallucinations que pour la paranoïa : en effet, il ressort qu'un certain nombre de détenus répondent positivement aux signes cliniques de la paranoïa (facteur « paranoïa ») alors qu'il s'agit de méfiance envers la surveillance policière.…”
Section: Résultatsunclassified
“…Cela est plus significatif pour les hallucinations que pour la paranoïa : en effet, il ressort qu'un certain nombre de détenus répondent positivement aux signes cliniques de la paranoïa (facteur « paranoïa ») alors qu'il s'agit de méfiance envers la surveillance policière. En outre, les idées suicidaires sont liées au manque de support de l'entourage [31,14] et à l'histoire de tentative(s) de suicide personnelle [18,12]. En revanche, le lien entre les idées suicidaires et un deuil récent ou la ou les tentative(s) de suicide dans la famille n'est pas significatif.…”
Section: Résultatsunclassified
See 2 more Smart Citations